Too many to count: Using orthophotography to census an unharvested beaver (Castor canadensis) population in Ontario. Issue 7 (19th July 2022) - McLaren, A. A. D.; Newton, E. J.; Silver, A.; Allan, M. R.; Middel, K. R.; Pond, B. A.; Patterson, B. R.
Abstract: Various methods exist to monitor wildlife populations and estimate trends in their distribution and abundance. For American beaver ( Castor canadensis ), aerial surveys provide a means to obtain abundance data over large areas and typically involve observers searching watercourses and shorelines for active beaver presence. Here, we describe a systematic aerial photographic census we designed and executed in autumn to quantify annual beaver colony abundance on the 184‐km 2 Michipicoten Island, Ontario, from 2015 to 2019. Aerial photographs were stitched together into orthophotomosaics after each census and visually searched for beaver food caches, with each food cache representing an independent beaver colony. Our methods revealed that beaver colony abundance declined substantially from a peak of 6.1 colonies/km 2 in 2015, the highest reported across North America, to 0.4 colonies/km 2 in 2018. Beaver abundance remained low through 2019. Although photographing the entire isolated study area required relatively little time and effort, even when beaver density was very high, post‐census processing work was time‐consuming. Lessons learned will improve efficiencies of our future censuses and aid other researchers. Our method is advantageous over traditional aerial wildlife surveys in that it provides a digital and visual record that can be used for additional analyses.